A Separated two stage helium liquefier using a 4 K GM cryocooler. (April 2019) - Liu, Mengyu; Zuo, Huakun; You, Jun; Li, Liang; Wang, Shaoliang
Abstract: A small-scale helium liquefier using a GM cryocooler (1.5 W @ 4.2 K) is designed and built. The helium gas to be liquefied is precooling by the cryocooler with natural convention loop and the precooling process inside the liquefier is separated to two stages by the first stage cold head of the cryocooler. Liquid nitrogen is used for cooling helium gas before entering the liquefier and cooling the radiation shield as well. The liquefier can start producing liquid helium within 7.5 hours after running from room temperature. A liquefaction rate of 18.57 L/day is obtained at a working pressure of about 115 kPa. Simply designed with high performance makes this helium liquefier appropriate to be used directly with cryostats for scientific experiments of liquid helium temperature range.